(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
The clothing pressure of tight seamless sportswear restricts wearer’s movement and causes discomfort. In this paper, a research on the dynamic pressure comfort of tight seamless sportswear is conducted. The study samples are four men’s sportswear of an ordinary style. They are made of same material with same style and cylinder diameter but with different organization structure and knitting methods. The dynamic pressure and pressure sense of different positions in tight seamless sportswear are tested by young men of similar body sizes. In combination with fuzzy mathematics and box control graph, the methods of objective and subjective evaluation are used to describe the pressure of positions and garments, and to summarize the relationship between pressure and comfort. The study will provide some useful guidance for design and production of tight seamless sportswear.